1988
DOI: 10.1007/bf00580863
|View full text |Cite
|
Sign up to set email alerts
|

Three types of calcium channels in the membrane of mouse sensory neurons

Abstract: Three types of electrically-operated calcium channels have been identified in the membrane of cultured dorsal root ganglion neurons from mouse embryos using patch clamp technique. Low-threshold inactivating (LTI) channels with the lowest unitary conductance (5.7 pS with 60 mM Sr2+ or 7.2 pS with 60 mM Ba2+) preserved their activity for a long time on excised membrane patches and were insensitive to dihydropyridine Ca channel agonist Bay K8644. Corresponding whole-cell current could be decreased by 40% with 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 22 publications
9
49
0
2
Order By: Relevance
“…Primary sensory neurons express multiple types of Ca 2ϩ channels, including T-, N-, P/Q-, R-, and L-types (Fedulova et al, 1985;Fox et al, 1987;Kostyuk et al, 1988;Regan et al, 1991;Mintz et al, 1992). From our data, it is not clear which type(s) of HVA Ca 2ϩ channels is subjected to the inhibition after activation of hSNSR4, although one assumes that N-and P/Q-type Ca 2ϩ channels are involved because these channel types are highly modulated by GPCRs.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Primary sensory neurons express multiple types of Ca 2ϩ channels, including T-, N-, P/Q-, R-, and L-types (Fedulova et al, 1985;Fox et al, 1987;Kostyuk et al, 1988;Regan et al, 1991;Mintz et al, 1992). From our data, it is not clear which type(s) of HVA Ca 2ϩ channels is subjected to the inhibition after activation of hSNSR4, although one assumes that N-and P/Q-type Ca 2ϩ channels are involved because these channel types are highly modulated by GPCRs.…”
Section: Discussionmentioning
confidence: 71%
“…DRG neurons express many types of voltage-dependent Ca 2ϩ channels (Fedulova et al, 1985;Kostyuk et al, 1988;Fox et al, 1987;Regan et al, 1991;Mintz et al, 1992;Yusaf et al, 2001), and as shown in Figure 1, the composition of I Ca varies considerably from cell to cell. To separate the effects of BAM8 -22 on I Ca arising from LVA and HVA Ca 2ϩ channels, a voltage protocol consisting of 30 msec test pulses to Ϫ40 mV and ϩ10 mV evoked from a holding potential of Ϫ80 mV was used ( Fig.…”
Section: Camentioning
confidence: 99%
“…Unresolved questions include the following: Does the voltage dependence of the mean open time explain the slowly deactivating tail currents observed at the whole cell level (64)? One study found that open times were shorter at more negative test potentials (64), another found no difference (104), while two found that they increased (217,368). To complicate matters more, two studies have found evidence for a second type of opening of longer duration (27,147).…”
Section: J Single-channel Recordingsmentioning
confidence: 99%
“…To examine this hypothesis, the ability of Rem2 to modulate endogenous voltage-activated Ca 2ϩ channels in primary sensory neurons of DRGs was examined. Unlike SCG neurons, DRG neurons express both LVA and HVA Ca 2ϩ channels (Fedulova et al, 1985;Kostyuk et al, 1988;Regan et al, 1991;Mintz et al, 1992;Yusaf et al, 2001). Because large functional T-type currents are recorded from cells expressing only the Ca V a 1 3.x subunit, it is assumed that .Gi1-10aa,The first 10 residues of G␣ i1 ; K-ras4B-c-tail, the last 23 residues at the C-end of K-ras4B; Uninj., uninjected.…”
Section: Specificity Of Rem2 For High-voltageactivated Camentioning
confidence: 99%